The Impact of Intergenerational Relationship on Health and Well‐Being of Older Chinese Americans. (12th August 2019) - Lai, Daniel W.L.; Lee, Vincent W.P.; Li, Jia; Dong, XinQi
Abstract : BACKGROUND/OBJECTIVES: Among older adults, intergenerational support can help to improve well‐being. This study examines the correlation between intergenerational relationships and the subjective well‐being among older Chinese immigrants in the United States. DESIGN: Hierarchical multiple regression analyses were applied to test the association between intergenerational relationships and self‐rated well‐being. The mediating effects of sense of control and the moderation effects of support from friends were also tested. SAMPLE: A cross‐sectional sample of 2717 older Chinese immigrants, aged 60 years and older, with children and grandchildren was drawn from the Population Study of Chinese Elderly. MEASUREMENTS: Study measures included four items concerning intergenerational relationships: the Pearlin Mastery Scale, two items on seeking support from friends, and single items measuring self‐rated health status and quality of life. RESULTS: Only the feeling of closeness with children was positively linked with subjective well‐being, while coresidence and frequency of talking were not. Support from friends moderated the association with self‐rated health status, while sense of control partially mediated the association between feeling of closeness and both self‐rated health status and quality of life. CONCLUSION: A stronger sense of closeness with children correlates to self‐rated health status and quality of life among older Chinese immigrants. The effects of sociocultural changes affecting Chinese American families, and potential implications for older adults' health, could be addressed through strategies to develop emotional closeness with their families and to support sense of control and well‐being among older Chinese adults. J Am Geriatr Soc 67:S557–S563, 2019.